2015
DOI: 10.1007/s10118-015-1669-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly and pH-responsive properties of poly(L-glutamic acid-r-L-leucine) and poly(L-glutamic acid-r-L-leucine)-b-polysarcosine

Abstract: Polypeptides and polypeptoids were widely used as biomedical materials because of their good biocompatibility. In this work we reported a series of pH-responsive copolypeptides and polypeptide-polypeptoid block copolymers, i.e. random copolymers of L-glutamic acid (Glu) with L-leucine (Leu) [poly(Glu-r-Leu)s], as well as their block copolymers with polysarcosine (polySar). Well-defined poly(Glu-r-Leu)s with predictable compositions and molecular weights were synthesized by ring opening polymerization of corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…8). The change trend is consistent with the research consequence of Tian [11], but inconsistent with Li [12]. During natural dormancy, soluble protein content decreased, probably because jujube tree had entered deep dormancy and the low temperature hindered the synthesis of protein or accelerated the hydrolysis of protein.…”
Section: Resultssupporting
confidence: 67%
“…8). The change trend is consistent with the research consequence of Tian [11], but inconsistent with Li [12]. During natural dormancy, soluble protein content decreased, probably because jujube tree had entered deep dormancy and the low temperature hindered the synthesis of protein or accelerated the hydrolysis of protein.…”
Section: Resultssupporting
confidence: 67%
“…Polymerization methods provide new insights in the synthesis of peptide/peptoid hybrids with high molecular weight and different structures such as block, random and alternating polymer structures. Many studies were reported about the sequential synthesis of peptide/peptoid hybrid polymer with block structure by ring-opening polymerization of 𝛼-NCAs (Figure 11), [54,[98][99][100][101] which had already been reviewed by Barz and Ling. [55,102] Polysarcosine with stealth-like properties was always used as peptoid block and combined with polypeptide block with functionality and stimuli-responsiveness.…”
Section: Polymerization Methodsmentioning
confidence: 99%
“…[11][12][13][14] However, fabrication of polymeric nanoparticles is usually a tedious and time-consuming process, which is often uneconomic and difficult to scale up. [15][16][17][18] Direct fabrication of nano-objects via polymerizationinduced self-assembly (PISA), which have been developed in recent years, [19][20][21][22][23][24][25][26] may be one of the best methods to solve this problem. PISA strategy allows fabricating of polymeric nanoparticles at much high concentrations, and has become a powerful strategy for fabrication of polymeric nanoparticles.…”
Section: Introductionmentioning
confidence: 99%